2017
DOI: 10.1016/j.jspr.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Can environmental dust from silo area allow the development of stored product insects?

Abstract: Dust derived from food processing can accumulate in places difficult to reach, where stored-product pests could thrive. The purpose of this work was to verify the development of Plodia interpunctella, Ephestia kuehniella, and Tribolium castaneum in dust collected on pipes and beams (15 m and 7.5 m) in a silo area of a pasta industry. Proximate analyses showed a higher metal content in the dust collected at the two different heights than semolina, including the presence of chrome, cobalt, arsenic, and lead. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Fruit flies have been proposed as a possible reservoir of this bacterium, as a strain of L. sanfranciscensis with 97% rDNA sequence similarity was reported in the gut of Drosophila simulans Stuvervant, a species of fruit fly closely related to Drosophila melanogaster (Groenewald et al, 2006). The presence of fruit fly in artisanal bakeries and plants corroborate this hypothesis (Locatelli, Savoldelli, Girgenti, Lucchini, & Limonta, 2017). A recent research showed the possibility that frass released by flies and grain beetles is a natural reservoir of this species, as L. sanfranciscensis was identified as a predominant species in fecal samples of Tribolium castaneum and Tribolium confusum larvae, the insects that infest stored cereal products, by sequencing 16S rRNA gene amplicons using the high-throughput Illumina MiSeq platform (Boiocchi et al, 2017).…”
Section: Prevalence Of L Sanfranciscensis In Sourdoughmentioning
confidence: 78%
“…Fruit flies have been proposed as a possible reservoir of this bacterium, as a strain of L. sanfranciscensis with 97% rDNA sequence similarity was reported in the gut of Drosophila simulans Stuvervant, a species of fruit fly closely related to Drosophila melanogaster (Groenewald et al, 2006). The presence of fruit fly in artisanal bakeries and plants corroborate this hypothesis (Locatelli, Savoldelli, Girgenti, Lucchini, & Limonta, 2017). A recent research showed the possibility that frass released by flies and grain beetles is a natural reservoir of this species, as L. sanfranciscensis was identified as a predominant species in fecal samples of Tribolium castaneum and Tribolium confusum larvae, the insects that infest stored cereal products, by sequencing 16S rRNA gene amplicons using the high-throughput Illumina MiSeq platform (Boiocchi et al, 2017).…”
Section: Prevalence Of L Sanfranciscensis In Sourdoughmentioning
confidence: 78%
“…As P. h. hilaris cultures are time-consuming to maintain, for assessment of the ability of the parasitoid to reproduce, we followed Abdi et al [ 65 ] and used C. cephalonica as factitious hosts. Larvae were reared on an artificial diet used to rear Lepidoptera associated with stored post-harvest products [ 83 ]. About two-hundred C. cephalonica eggs were added into a Petri dish (15 cm diameter × 2 cm height) half-filled with diet.…”
Section: Methodsmentioning
confidence: 99%
“…), and insects are the most widespread poikilotherm animals (Bullock ), we have supposed that the origin of sourdough lactobacilli and yeasts could be attributed to a faecal contamination of insects infesting stored cereal products and the common fruit fly, which is sometimes observed in artisanal bakeries and plants (Locatelli et al . , personal communication).…”
Section: Discussionmentioning
confidence: 98%
“…The artificial diet for the feeding of larvae constituted of 23·4% (w/w) glycerol, 18·4% honey, 17·9% corn meal, 16·6% bran, 15·1% wheat meal, 4·7% wheat germ and 3·9% yeast extract (Locatelli et al . ). In addition to the artificial diet, larvae of P. interpunctella were reared on grains of Triticum aestivum .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation